Capital Gain dalam Perspektif Ekonomi Syariah - indah kurniawati (Al-Kharaj: Journal of Islamic Economic and Business, 2020)
The purpose of this study is to determine capital gain in the Islamic economy. This research is a qualitative study. In Islamic economics, investment is a muamalah activity that is highly recommended, because investment funds are needed to be productive and also bring benefits to others. The Qur'an strictly forbids hoarding (ikhtinaz) ownership activities. An investor's profit in the stock game is obtained through capital gain by selling shares when the selling price is higher than the price previously bought.The results show that capital gain in Islamic economics are permissible as long as they are not sourced from al Gharar. If sourced al Gharar is forbidden because it contains maysir.Capital gain are also forbidden if a percentage of profits has been determined for each period